Historical predecessors and current geographical possibilities of ethnic based territorial autonomies in the Carpathian Basin - Kocsis, Károly (Hungarian Geographical Bulletin, 2013)
Despite the ethnic cleansings, deportations, forced assimilation, homogenization and partly due to the immigration of foreign-born population there is hardly any country in Europe which could be called ethnically homogeneous. This is particularly true in the case of the small „nation-states” of the Carpathian Basin (Hungary, Slovakia, Ukraine, Romania, Serbia etc). So, starting from the fact, that in ethnically diverse regions the territorial autonomies are one of the most eff ective tools of minority protection and confl ict solution, and are safeguards for ensuring the cultural survival and protection of collective rights of national minorities, this paper tries to outline the geographic background of existing (and missing) territorial autonomies in Europe (1st part) and, in more details, the historical predecessors and the geographical possibilities of ethnic based territorial autonomies in the Carpathian Basin (2nd part). Although the emphasis is largely laid on the contemporary situation, there are important sections devoted to the historical development of the ethnic based territorial autonomies in this geographic work as well.